Comparison of the effects of different physical activities on laterality and asymmetry values through side bridge test - Villalba, Marina Mello [UNESP] (2019)
Aim: To compare the effects of different physical activities on laterality and asymmetry values through the side bridge test. Methods: the assessments were carried out in 45 subjects between 18 and 30 years old, 15 Crossfittrained individuals, 15 weight trained and 15 sedentary. The subjects performed the side bridge test on both sides. After checking the normality and homogeneity of the data, we selected the appropriate statistical analysis for the comparison of the variables, adopting a significance level of α <0.05. Results: there was no statistical difference in the balance ratio; however, significant difference was found in the side bridge test endurance time, in which the Crossfit group obtained longer times on both sides than the other two groups. The side bridge test is a test of simple execution and that in this study the Crossfit group presented better results in the endurance time in the side bridge test. Conclusion: the results of the ratio asymmetry and endurance time are not sufficient to evaluate the resistance of the core muscles but could be an evaluation tool, the side bridge test can be introduced in postural training programs.